Consumption of dairy foods in relation to impaired glucose metabolism and type 2 diabetes mellitus: the Maastricht Study. Issue 8 (24th February 2016) - Eussen, Simone J. P. M.; van Dongen, Martien C. J. M.; Wijckmans, Nicole; den Biggelaar, Louise; Oude Elferink, Stefanie J. W. H.; Singh-Povel, Cécile M.; Schram, Miranda T.; Sep, Simone J. S.; van der Kallen, Carla J.; Koster, Annemarie; Schaper, Nicolaas; Henry, Ronald M. A.; et al.
Abstract: Observational studies suggest an inverse association between total dairy product intake and diabetes risk. However, there is a lack of information on the relationship of specific dairy products with impaired glucose metabolism (IGM) and type 2 diabetes mellitus (T2DM). Individuals aged 40–75 years were recruited for the Maastricht Study. All the participants filled out a 253-food item FFQ, covering fifty specific dairy items that captured differences between full-fat, semi-skimmed and skimmed products, as well as fermented and non-fermented products. Glucose metabolism status was assessed by an oral glucose tolerance test, and participants were informed on their glucose metabolism status after returning the FFQ. Data of 2391 individuals were available to estimate OR (95 % CI) for IGM ( n 470) and newly diagnosed (ND) T2DM ( n 125), with adjustment for age, sex, BMI, physical activity, smoking status, education, energy intake and intakes of vegetables, fruits, meat and fish. For IGM, fully adjusted analyses revealed inverse associations, with OR comparing the highest with the lowest tertile of intake of 0·73 (95 % CI 0·55, 0·96) for skimmed products and 0·74 (95 % CI 0·54, 0·99) for fermented products. These dairy products were not associated with ND T2DM. In contrast, full-fat products were positively associated with ND T2DM (OR 2·01; 95 % CI 1·16, 3·47), whereas total dairy product intake was inversely associated with ND T2DM (OR 0·50; 95 % CI 0·26, 0·93). In conclusion, individuals with a high consumption of skimmed and fermented products had lower odds of having IGM, and individuals with a high consumption of total dairy products had lower odds of having ND T2DM. High intake of full-fat products was not related to IGM but was positively related to ND T2DM.